Sawing Through The Neck - A Case of Serrated Fish Bone Migrating to Prevertebral Space - LX, Ngui; G., Shashi; AB., Muhammad Nasri (IIUM Medical Journal Malaysia, 2019)
Fish bone is the commonest pharyngeal foreign body, however migrating fish bone is a rare occurrence. We report a case of a 54-year-old male who had history of fish bone ingestion over a week and presented with odynophagia and worsening neck pain. Rigid esophagoscopy revealed tip of a fish bone which was embedded in granulation tissue. The fish bone migrated further with manipulation. Aided with computed tomography scan findings, the serrated fish bone was finally removed via transcervical approach without any complication. In conclusion, high index of suspicion and prompt removal of migrating fish bone with the aid of computed tomography imaging is necessary to avoid fatal complications.